2019
DOI: 10.1111/gbb.12619
|View full text |Cite
|
Sign up to set email alerts
|

Complex patterns of dopamine‐related gene expression in the ventral tegmental area of male zebra finches relate to dyadic interactions with long‐term female partners

Abstract: Dopaminergic projections from the ventral tegmental area (VTA) to multiple efferent targets are implicated in pair bonding, yet the role of the VTA in the maintenance of long-term pair bonds is not well characterized. Complex interactions between numerous neuromodulators modify activity in the VTA, suggesting that individual differences in patterns of gene expression in this region may explain individual differences in longterm social interactions in bonded pairs. To test this hypothesis we used RNA-seq to mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 68 publications
1
5
0
Order By: Relevance
“…Although one study showed dopamine release in the prefrontal cortex while viewing the face of a new romantic partner (Takahashi et al, 2015), here we used genetic markers to confirm direct involvement of dopamine in the midbrain/VTA. Interestingly, our results are consistent with a recent study which showed that dopamine-related gene expression in the VTA of male zebra finches was associated with pair-bonding behaviors (nesting and courtship) of their female pair (Alger et al, 2020). Also, individual differences in social interactions in long-term zebra finch pairs Other colored regions did not meet the statistical requirements for whole-brain analysis or were not an ROI.…”
Section: Discussionsupporting
confidence: 88%
“…Although one study showed dopamine release in the prefrontal cortex while viewing the face of a new romantic partner (Takahashi et al, 2015), here we used genetic markers to confirm direct involvement of dopamine in the midbrain/VTA. Interestingly, our results are consistent with a recent study which showed that dopamine-related gene expression in the VTA of male zebra finches was associated with pair-bonding behaviors (nesting and courtship) of their female pair (Alger et al, 2020). Also, individual differences in social interactions in long-term zebra finch pairs Other colored regions did not meet the statistical requirements for whole-brain analysis or were not an ROI.…”
Section: Discussionsupporting
confidence: 88%
“…The observer conducted daily 20 min observations of each established pair in a random order for 5 days (Days 17–21 after pairing). We selected this observation frequency and duration based on our past studies in European starlings and zebra finches in which 20 min observations across 4–5 days revealed strong correlations between behavior and neuronal markers, including mRNA (e.g., Alger et al, 2011, 2020; DeVries et al, 2015; Kelm et al, 2011) and a survey of observation durations in zebra finches which range from 5 to 15 to 30 min in different studies (Banerjee et al, 2013; Bolund et al, 2012; Tomaszycki & Adkins-Regan, 2006). Observations began between 30 min and 5 h 30 min after the lights turned on.…”
Section: Methodsmentioning
confidence: 99%
“…DIFFERENCES IN DOPAMINE AND OPIOID RECEPTOR RATIOS Alger et al, 2011Alger et al, , 2020DeVries et al, 2015;Kelm et al, 2011) and a survey of observation durations in zebra finches which range from 5 to 15 to 30 min in different studies (Banerjee et al, 2013;Bolund et al, 2012;Tomaszycki & Adkins-Regan, 2006). Observations began between 30 min and 5 h 30 min after the lights turned on.…”
Section: Behavioral Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…But how do females select a male partner? Alger et al address this question in zebra finches, using computational approaches to identify subgroups of males that exhibit distinct patterns of gene expression in the ventral tegmental area (VTA). Intriguingly, these divisions were most tightly predictive of the behavior of the male's female partner, even more so than the behavior of the male himself.…”
mentioning
confidence: 99%